PRIZE LOTS IN ISLAMIC PERSPECTIVE (Case Study of Lucky Draw at Bank BNI Syariah KCP Ampel Surabaya) - Layyinah Layyinah; Umi Chabibah; Anisa Solikhawati; Abdul Hakim; Siti Musfiqoh (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2018)
Abstract This study aims to find out more about the law of prize lots according to the Islamic perspective. The prize lots with prizes is increasingly prevalent in the community, and is becoming a familiar thing. Prize lots is one form of allowing products in an institution, especially in the banking world. Prize lots in BNI Syariah banks is carried out to attract customers to transact using Syariah Banks. This study uses a qualitative method based on literacy theory and methods. This study is based on the laws that exist in the Qur'an, hadith, and fiqh rules that allow Prize lots with terms and conditions that do not come out of Islamic teachings. In this study, the practice of the iB Hasanah BNI Syariah Savings Prize lots is that the customer opens an iB Hasanah Savings account at Bank BNI Syariah KCP Ampel Surabaya and if the customer has a minimum balance or meets the requirements to participate in the lucky draw, the bank will automatically provide a lottery number for entered in a lottery to determine which customers are entitled to receive prizes. From this study, the authors can conclude that the practice of Prize lots with iB Hasanah Savings at Bank BNI Syariah KCP Ampel Surabaya is not a gambling practice (maysīr) which is forbidden by Islam because the practice does not fulfill the elements of gambling, namely the presence of a party who bets, the determination of the winner. and done face to face. Keywords: Prize lots, Lucky Draw, Islamic Bank, Prize Abstrak Penelitian ini bertujuan untuk mengetahui lebih tentang hukum undian berhadiah menurut perspektif Islam. Undian berhadiah semakin marak di masyarakat, dan menjadi hal yang tidak asing lagi. Undian berhadiah menjadi salah satu bentuk memperkenankan produk di suatu lembaga, utamanya dalam dunia perbankan. Undian berhadiah dalam bank BNI Syariah dilakukan agar menarik nasabah untuk bertransaksi menggunakan Bank Syariah. Penelitian ini menggunakan metode kualitatif yang berlandaskan teori dan metode literasi. Penelitian ini didasarkan pada hukum yang ada di Al-Qur’an, hadits, dan kaidah-kaidah fikih yang membolehkan undian berhadiah dengan syarat dan ketentuan yang tidak keluar dari ajaran Islam. Dalam riset ini, praktik Undian Berhadiah Tabungan iB Hasanah BNI Syariah adalah nasabah membuka rekening Tabungan iB Hasanah di Bank BNI Syariah KCP Ampel Surabaya dan apabila nasabah telah memiliki saldo minimum atau memenuhi persyaratan untuk mengikuti undian berhadiah maka secara otomatis pihak bank akan memberikan nomor undian untuk diikutkan dalam undian untuk menentukan nasabah mana yang berhak mendapatkan hadiah. Dari penelitian ini, penulis dapat menyimpulkan bahwa praktik undian berhadiah Tabungan iB Hasanah pada Bank BNI Syariah KCP Ampel Surabaya bukanlah merupakan praktik judi (maisir) yang diharamkan oleh Islam karena praktek tersebut tidak memenuhi unsur-unsur judi yaitu adanya pihak yang bertaruh, adanya penentuan pemenang dan dialkukan secara berhadap-hadapan langsung. Kata Kunci : Undian Berhadiah, Bank Syariah, Hadiah